An Analysis of Grammatical Errors on "Twitter" - Monica Heraldine; Nurma Dhona Handayani (Humanitatis : Journal of Language and Literature, 2022)
This research was conducted to find out about the grammatical errors on Twitter. This research used descriptive qualitative research to aimed the types of grammatical errors by using the strategy taxonomy by Dulay, Burt, and Krashen that was realized on Twitter. The method of collecting the data in this research used the observational method. And the purpose of this research was to identify and describe the types of grammatical errors on Twitter. Thus, the researcher found 4 types of grammatical errors, those were 4 data of addition with a percentage 26.7%, then for the second type was 6 data of omission with a percentage 40%, the third type was 3 data of misformation with a percentage 20%, and for the last were 2 data of misordering with the percentage 13.3%. For the data result, it can be concluded that the most types of grammatical errors on Twitter were omission types with 6 data and a percentage 40%.